Pertanggungjawaban Pidana Korporasi Penyedia Konten Pornografi Anak - Ika Dewi Sartika Saimima; Fransiska Novita Eleanora; Widya Romasindah (Faculty of Law Hang Tuah University, 2019)
The rise of child crime is increasing, even using networks on socialmedia (Facebook), the culprit is not only personal, but also the corporation, inhandling it using Law Number 11 of 2008 concerning Information and ElectronicTransactions (ITE), by looking at forms of criminal liability corporation in child pornography content providers. the purpose of the study is to find out the criminal liability of the corporation providing the content of child pornography, and to know the obstacles in the prevention of child sexual crime (social media) through internet media. The results obtained were more emphasizing and directing the accountability of corporations providing child pornography content (official loly candy; s group case studies), and the penalties given to perpetrators could provide: deterrent effects and were given punishments in the form of actions and rehabilitation to perpetrators, and the law Indonesia in tackling child crime on social media